Challenges Encountered by 0ne-year Diploma student midwives in acquiring clinical skills at selected hospitals in Limpopo Province - Manthata, Joyce Maphuti (University of Limpopo, 2016)
Introduction and purpose: Midwives are the backbone of maternal and child health—the output of their action affect quality of life of mother and child. The purpose of the study was to describe the challenges encountered by one-year diploma student midwives while acquiring clinical skills at selected hospitals in Limpopo Province. Research design and method: A quantitative, descriptive cross-sectional research method was used in this study. The study population comprised all one-year diploma student midwives in selected hospitals in Limpopo Province, namely, Dilokong Hospital, Jane Furse Memorial Hospital, Mokopane Hospital, Philadelphia Hospital, Siloam Hospital and St Rita’s Hospital. The whole study population was used as the total population was small. Data were collected using a self-administered questionnaire. Informed consent was received from the participants as was ethical approval from the relevant authorities. Data were analyzed using SPSS version 22 with the aid of a statistician. Descriptive statistics were used to analyze and describe the data. Data were presented in tables and bar graphs.Findings: Respondents in this study indicated that they encountered the following challenges during their acquisition of clinical skills at the selected hospitals in the Limpopo Province: inadequate resources; inadequate mentoring. Male participants reported feelings of being more competent than their female counterparts. There was no relationship between acquisition of skills and marital status, and no correlation between age and acquisition of skills.
Thesis (MPH.) -- University of Limpopo, 2016.
Keywords: Challenges; One-year diploma; Enrolled nurse; Student midwives; Acquiring clinical skills.; Encounter; Clinical competence; Midwives -- South Africa; Health Promotion